Electronic Transfer: A Good Investment - Terry W. Canup (Journal of Applied Communications, 1984)
Instead of debating whether use of computers in information offices is overrated or underrated, it may be more constructive for agricultural communicators to accept computerization as inevitable and weigh the advantages and disadvantages of jumping into different aspects of computerization now.